METABOLIC BASIS OF URINARY TRACT INFECTION PROPHYLAXIS IN CHILDREN - N. B. Kuprienko; Z. V. Svetlova; N. N. Smirnova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
The most essential data, predisposing to onset and recurrence of urinary tract infection in children are included in the review. Mineral, carbohydrate and purin metabolism monitoring both in active stage and remission of pyelonephritis is necessary for elaboration individual schemes of primary and secondary prophylaxis of chronic renal disease in children.